Case Report: Exome sequencing reveals recurrent RETSAT mutations and a loss-of-function POLDIP2 mutation in a rare undifferentiated tongue sarcoma [version 1; referees: 2 approved] - Jason Y. K. Chan; Peony Hiu Yan Poon; Yong Zhang; Cherrie W. K. Ng; Wen Ying Piao; Meng Ma; Kevin Y. Yip; Amy B. W. Chan; Vivian Wai Yan Lui (F1000Research, 2018)
Soft tissue sarcoma of the tongue represents a very rare head and neck cancer with connective tissue features, and the genetics underlying this rare cancer are largely unknown. There are less than 20 cases reported in the literature thus far. Here, we reported the first whole-exome characterization (>×200 depth) of an undifferentiated sarcoma of the tongue in a 31-year-old male. Even with a very good sequencing depth, only 19 nonsynonymous mutations were found, indicating a relatively low mutation rate of this rare cancer (lower than that of human papillomavirus (HPV)-positive head and neck cancer). Yet, among the few genes that are somatically mutated in this HPV-negative undifferentiated tongue sarcoma, a noticeable deleterious frameshift mutation (with a very high allele frequency of >93%) of a gene for DNA replication and repair, namely POLDIP2 (DNA polymerase delta interacting protein 2), and two recurrent mutations of the adipogenesis and adipocyte differentiation gene RETSAT (retinol saturase), were identified. Thus, somatic events likely affecting adipogenesis and differentiation, as well as potential stem mutations to POLDIP2, may be implicated in the formation of this rare cancer. This identified somatic whole-exome sequencing profile appears to be distinct from that of other reported adult sarcomas from The Cancer Genome Atlas, suggesting a potential unique genetic profile for this rare sarcoma of the tongue. Interestingly, this low somatic mutation rate is unexpectedly found to be accompanied by multiple tumor protein p53 and NOTCH1 germline mutations of the patient’s blood DNA. This may explain the very early age of onset of head and neck cancer, with likely hereditary predisposition. Our findings are, to our knowledge, the first to reveal a unique genetic profile of this very rare undifferentiated sarcoma of the tongue.